The Impact of Streaming Services on Cinema Film Consumption in the Czech Republic - Fecková, Barbora; Escobar Rios, Andrea; Bahles, Michael; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
The rapid growth of streaming services has significantly impacted the global film industry, challenging traditional cinema and altering consumer behaviour and distribution strategies. This thesis investigates the impact of streaming services on the behaviour of cinema-goers in the Czech Republic, aiming to identify unique aspects of the cinematic experience. The findings provide valuable insights for refining marketing strategies for foreign films in the local context. Drawing on a comprehensive literature review and primary research into film consumer behaviour, cinema-going preferences, and attitudes toward streaming platforms conducted through a questionnaire, the findings reveal that while streaming services dominate film consumption habits in Czechia due to their convenience and vast content libraries, the cinema experience retains a unique appeal, particularly for high-profile films, as Czech audiences value the immersive environment and social aspects of theatrical viewing. Factors influencing cinema attendance include genre, plot, and critical acclaim, while traditional advertising methods like TV and radio are less impactful than audiovisual tools such as trailers. Many respondents support a cinema-first release strategy for major films, suggesting that streaming and cinemas can coexist through hybrid distribution models. These insights provide actionable recommendations for film distributors and marketers to tailor strategies that balance the strengths of streaming services and traditional cinemas, ensuring the continued viability of theatrical releases in the Czech market.
Vedoucí práce: Andrea Escobar Rios
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses